Concentracion de metanol en vinos sueltos procedentes de Cascas, 2016 - Otoya Lavado, Sthefany Yanitza (2016)
This research main objective was to determine the concentration of methanol in loose wine cellars expended in 2016 Cascas district. A quantum chemical method to first determine the presence of methanol in the 20 samples of wine, 2 different wineries which were classified according to their type of wine (red, white and pink) and as sugar was used for this research each wine (sweet, semi-dry and dry), respectively in a presentation bottle 1 liter. The results showed that wine samples only the presence of ethanol were not methanol so only proceeded make up the qualitative method, therefore it was concluded that the presence of methanol in the wine samples are negative and are unfit for human consumption